Effect of mortar grade on the uniaxial compression strength of low-strength hollow concrete block masonry prisms. (2020) - Syiemiong, Hopeful; Marthong, Comingstarful
Abstract: Locally-produced, low-strength hollow concrete blocks are inadvertently used in masonry construction due to their low cost and ease of manufacture. An experimental study was conducted to study the effect of mortar strength on the uniaxial compressive strength characteristics of masonry prisms constructed with low-strength hollow concrete blocks. The concrete blocks are produced locally by using the stone aggregates obtained from wastes of stone quarries. Three types of mortar grades (cement-sand ratio) were used in the study, i.e., 1:3 (strong mortar), 1:4.5 (moderate mortar) and 1:6 (weak mortar). From the results and observations, the stress-strain curves of low-strength masonry prisms have been obtained. A relation between the modulus of elasticity of low-strength hollow-concrete block masonry prisms and their compressive strengths have also been obtained. It is observed that the use of higher strength mortar does not have a marked effect on the prism strength of low-strength hollow concrete blocks masonry prisms.